2018
DOI: 10.1136/bmjsem-2017-000314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-week running programme in youth and adults with complex mood disorders

Abstract: ObjectiveAlthough numerous studies suggest a salutary effect of exercise on mood, few studies have explored the effect of exercise in patients with complex mental illness. Accordingly, we evaluated the impact of running on stress, anxiety and depression in youth and adults with complex mood disorders including comorbid diagnoses, cognitive and social impairment and high relapse rates.MethodsParticipants were members of a running group at St Joseph Healthcare Hamilton’s Mood Disorders Program, designed for clie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 39 publications
3
19
1
4
Order By: Relevance
“…In the current study, we observed improvements in general health and all mental health HRQOL subscales, which is consistent with the literature 63–65. Further, the observed social functioning improvements build on our previously published finding of improved perceived friendship in an overlapping sample 29. To the best of our knowledge, this is the first study to report positive changes across multiple functional outcomes in a complex psychiatric sample of patients with mood disorders who, at baseline testing, were unemployed and/or struggling with school, had experienced multiple past episodes of depression, and were not being managed effectively by medications.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the current study, we observed improvements in general health and all mental health HRQOL subscales, which is consistent with the literature 63–65. Further, the observed social functioning improvements build on our previously published finding of improved perceived friendship in an overlapping sample 29. To the best of our knowledge, this is the first study to report positive changes across multiple functional outcomes in a complex psychiatric sample of patients with mood disorders who, at baseline testing, were unemployed and/or struggling with school, had experienced multiple past episodes of depression, and were not being managed effectively by medications.…”
Section: Discussionsupporting
confidence: 92%
“…Data were collected from 18 participants from August 2012 to December 2016 across 10 cohorts (see table 1). Although the youth group had an earlier age of onset and higher dropout rate than the adult group, previous analyses using a larger data set indicated no difference in youth compared with adult runners in terms of mood outcomes 29. Further, the rates of MDD and BD were similar in both groups (71.4% and 14.2% compared with 81.8% and 9.1% for adult and youth groups, respectively); therefore, the groups were analysed together.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Keating et al [142] (11,186) = 2.3, p = 0.01) from baseline was observed. Following intervention, mean depression scores decreased by 39% in adults from high to low levels and by 27% in youths from moderate to reduced moderate levels.…”
Section: Category 3: Longer-term Interventionsmentioning
confidence: 86%